INNOVATOR’S RACE: EXAMINING THE IMPACT OF A GAMIFIED BOARD GAME ON ENGINEERING STUDENTS’ LEARNING IN TECHNOLOGY ENTREPRENEURSHIP AND NEW PRODUCT DEVELOPMENT - Shafie, Dalili Izni (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Teaching Technology Entrepreneurship and New Product Development (NPD) to engineering students is challenging due to the abstract, multidisciplinary, and process-oriented nature of the subject, which often limits engagement and meaningful learning in lecture-based delivery. This study examines the impact of Innovator’s Race, a gamified board game developed as a teaching and learning innovation for ENT600 (Technology Entrepreneurship), designed to simulate the end-to-end entrepreneurship and NPD process in an interactive and learner-centred format. Using a quantitative approach, data were collected from 60 engineering students through a structured questionnaire. Descriptive statistics and reliability analyses were conducted using SPSS, followed by PLS-SEM to test a mechanism-based learning framework. The results show that gamified board game–based learning significantly enhances student engagement, conceptual understanding, entrepreneurial skill development, and learning motivation and confidence. However, mediation analysis indicates an indirect-only effect, whereby the impact of the gamified intervention on overall learning impact is transmitted exclusively through learning motivation and confidence rather than through direct instructional effects. The findings extend experiential learning research by demonstrating that gamified entrepreneurship education influences learning impact primarily through affective mechanisms. This study advances teaching and learning innovation by uncovering the central mediating role of students’ motivation and confidence in shaping engineering students’ entrepreneurship learning impact.